Decentralized Leadership - Emilson C.D. Silva (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper studies the efficiency of decentralized leadership in federations where selfish regional governments provide regional and federal public goods and the benevolent central government implements interregional earmarked and income transfers. Without residential mobility, unlimited decentralized leadership is efficient only if the center implements redistributive interregional income and earmarked transfers to equate consumption of private and regional public goods across regions. Such policies perfectly align the incentives of the selfish regional governments. With imperfect residential mobility, decentralized leadership is efficient if the center adopts redistributive interregional income and earmarked policies and there is a common labor market in the federation.
Keywords: C72; D62; D72; D78; H41; H77; H87; Q28; R30; R50; 330; decentralized leadership; earmarked transfers; common labor market; rotten kids